Effect of repeated morphine withdrawal on spatial learning, memory and serum cortisol level in mice - Matinfar, Mahdieh (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: One of the serious problems that opioid addicted people are facing is repeated withdrawal syndrome that is accompanying with a significant stress load for addicts. Therefore, the aim of this study was to evaluate the effects of repeated withdrawal on spatial learning, memory and serum cortisol levels in morphine-dependent mice. MATERIALS AND METHODS: Male NMRI mice received morphine as daily increasing doses for 3 days. After that, the mice underwent one time or repeated spontaneous or pharmacologic (naloxone-precipitated) withdrawal. Then spatial learning and memory were investigated by morris water maze test, and at the end trunk blood samples were collected for measurement of serum cortisol levels. RESULTS: The results showed that only repeated spontaneous withdrawal significantly increases escape latency (P < 0.05), and in other models of withdrawal, spatial learning and memory were intact. The results of probe trial were intact in all groups. Radioimmunoassay showed that serum cortisol levels were increased significantly in all models of withdrawal (P < 0.05 and P < 0.01) except the repeated spontaneous withdrawal. CONCLUSION: The results showed that short periods of withdrawal syndrome can increase serum cortisol levels; however they do not affect spatial learning and memory. Nevertheless, repeated spontaneous withdrawal can make learning slow.